If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4s + -5(7 + 6s) = 0 -4s + (7 * -5 + 6s * -5) = 0 -4s + (-35 + -30s) = 0 Reorder the terms: -35 + -4s + -30s = 0 Combine like terms: -4s + -30s = -34s -35 + -34s = 0 Solving -35 + -34s = 0 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '35' to each side of the equation. -35 + 35 + -34s = 0 + 35 Combine like terms: -35 + 35 = 0 0 + -34s = 0 + 35 -34s = 0 + 35 Combine like terms: 0 + 35 = 35 -34s = 35 Divide each side by '-34'. s = -1.029411765 Simplifying s = -1.029411765
| 4(1.5c+6)-2=-9 | | -104-7x=4x+61 | | x+4.3=55.4 | | 14+8g+9+2g-g=41 | | -8+2d=8 | | p=2*93+2*104 | | h=-16t^2+32t+3 | | 8x+14y=4-6-6X-7Y+-10 | | -4-y=12 | | 6*x+.14=.29 | | 20-1+(2-4)= | | 6c+24-2c=-9 | | y-3.5=.5x-4 | | (8-0.8)= | | (8-0.8)= | | 5x-2+9x=18 | | 0.80(x-100.00)=450. | | t-18=17 | | 3x+2-x=-3x-6 | | ln(2x+1)-ln(x-3)=1 | | 25b^2+40b+12=0 | | 14+8g+9+2g-g=49 | | -9n=-36 | | Y+15=11whatisy | | 5-6x+3=38 | | y-(-3)=-2x-5 | | 2(m-8)+9=3(4-m)-4 | | f(2c)=3(2c^2)+6(2c) | | -7.8=-1.4x+2 | | 6+4=120 | | -4p-5.2=11.1 | | 4x-13x-19=-73 |